2011
DOI: 10.1111/j.1365-2621.2011.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the microbial changes during koji‐making process of Douchi by culture‐dependent techniques and PCR‐DGGE

Abstract: Douchi as a traditional fermentation soyfood with an acquired taste had been appreciated by consumers for thousands of years in China and few Asian countries. Unfortunately, few studies had been conducted on the changes of microbial community during the koji-making process, and whether the pathogenic microorganisms involving the fermentation process is still unclear. Therefore, the PCR-denaturing gradient gel electrophoresis (DGGE) targeting the 16S and 18S rRNA genes was applied to characterise the dynamic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 20 publications
(33 reference statements)
6
37
2
Order By: Relevance
“…Diversity indices indicated that the diversity of the bacterial community increased as the koji making stage progressed, consistent with a previous report [25]. However, bacterial diversity then declined during the early stages of fermentation, before gradually recovering.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Diversity indices indicated that the diversity of the bacterial community increased as the koji making stage progressed, consistent with a previous report [25]. However, bacterial diversity then declined during the early stages of fermentation, before gradually recovering.…”
Section: Resultssupporting
confidence: 90%
“…Traditional Chinese medicine also uses douchi for treating dyspepsia, restlessness, asthma, and to increase sweating [2,3]. Recent studies indicated that douchi can inhibit prostate and breast cancer [4], and it also displays anti-diabetic activity [5] and protects against osteoporosis and cardiovascular diseases [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total bacteria -ATTACCGCGGCTGCTGG- (Chen et al, 2011a;Chen et al, 2011b;Jeyaram et al, 2008;Wang and Lee, 1997) 518…”
Section: Target Organism Primer Sequence(----) Referencementioning
confidence: 99%
“…During processing, the background was subtracted, differences in the intensity of the lanes were compensated during normalization and the correlation matrix was calculated. Clustering was done with Pearson correlation and the un-weighted pair group method with arithmetic mean (UPGMA) method (Chen et al, 2011a). When analyzing genetic diversity, Richness (S), ShannonWiener indices (H') and Evenness (E) were used according to the following equations (Luo et al, 2004):…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge) Analyzementioning
confidence: 99%